(untitled) (International Journal of Computer Science and Engineering, 2026)
Driven by the imperative of expanding new quality productive forces, this paper examines the intricate mechanism through which traditional industries navigate digital transformation, with a specific focus on constructing synergistic paths across multi-dimensional industrial ecosystems. While existing paradigms often treat digital adaptation as a linear technological upgrade, our empirical field investigations and structural modeling reveal a highly non-linear trajectory fraught with systemic inertia and coordination bottlenecks during initial implementation. Considering these structural impediments, we present a multi-layered framework that integrates resource reconfiguration, technological embedding, and institutional alignment. The gathered data suggest that digital proficiency does not automatically yield ecosystem synergy; rather, the conversion efficiency is likely moderated by regional economic disparities and varying degrees of data governance maturity, suggesting alternative interpretations regarding structural resistance. Consequently, the proposed paths provide a nuanced understanding of how traditional sectors might achieve high-quality development, though further empirical verification remains necessary to assess long-term adaptability across diverse regulatory environments. This exploration ultimately shifts the theoretical discourse from isolated corporate digitalization to a holistic ecosystem orchestration paradigm, shedding light on potential mechanisms for sustainable industrial evolution.